Cardiac Fibroelastoma versus Thrombus: Echocardiographic Evidence Can Be Misleading. (31st July 2016) - O'Laughlin, John P.; Verma, Gautam; Gulkarov, Iosif
Abstract : We present a case of a young female with stroke symptoms who underwent valve sparing resection of a presumed fibroelastoma based on echocardiographic findings. After confirming embolic stroke, she underwent excision of the lesion, which on pathology revealed a nonbacterial thrombus. Ultimately, this led to a more extensive work-up leading to the discovery of a papillary serous ovarian carcinoma, the underlying cause of her hypercoagulable state. The initial echocardiographic findings painted the clear picture of a papillary tumor on the aortic valve which was likely the source of the emboli resulting in ischemic stroke. This unique case presentation illustrates that imaging, including echocardiography, may not always coincide with the clinical diagnosis. Thus, understanding the differential diagnoses of cardiac masses is of vital clinical significance. The distinction of fibroelastoma versus the much less common finding of aortic thrombus may lead to early diagnosis of malignancy and prevention of life threatening events due to stroke or undiagnosed disease.